Режим ріки Дніпро в контексті гармонізації водного законодавства України із законодавством Європейського Союзу - Чернявська, О.Л. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Определены основные принципы гармонизации водного законодательства Европейского Союза, прежде всего в сфере защиты экологии водных бассейнов, с национальным законодательством. В статье перечислены основные правовые акты ЕС, подлежащие перенесению в национальное правовое поле. Определяются проблемы и перспективы процесса приведения украинского водного права в соответствие нормам европейского сообщества. This article is dedicated to the main principles of harmonization of the water law of the European Union, namely the acts concerning the ecology of the water basins, with the national legislation. The main legal documents of the EU that are to be introduced into the legal space of Ukraine are listed. Problems and prospects of the process of approximation of the Ukrainian water law to the norms of the European community are determined.